Advanced MicroCT Analysis of Lacustrine Carbonate Reservoirs for Fluid Flow Simulation - Olga M. O. Araújo; Alessandra Silveira Machado; Davi F. Oliveira; Ricardo Tadeu Lopes (e-Journal of Nondestructive Testing)
A better and more comprehensive understanding of the internal structure of rocks and developing quantitative methods for their characterization remain significant challenges. MicroCT is a powerful tool for visualizing the internal structure of materials, enabling 3D visualization and quantitative analysis of complex pore networks in a non-destructive manner. Lacustrine carbonate rocks, such as coquinas, are important hydrocarbon reservoirs, often found in oil fields. However, the complexity and heterogeneity of these deposits pose significant difficulties in characterizing their internal structures, making reservoir description a challenging task. Utilizing digital data is essential for fluid flow simulation studies. In this study, we perform digital rock analysis to investigate fluid flow by solving the Navier-Stokes equations in representative elementary volume (REV), applying this methodology to different regions of the sample. Furthermore, we compare the results for absolute permeability as a function of porosity and anisotropy degree.